136k views
3 votes
Solve for x 4(2x-3)=-1-3x

2 Answers

0 votes

4(2x-3)=-1-3x

Multiply the bracket by 4

(4)(2x)(4)(-3)=-1-3x

8x-12=-1-3x

8x-12=-3x-1

Move -3x to the other side. Sign changes from -3x to +3x.

8x+3x-12=-1

11x-12=-1

Move -12 to the other side. Sign changes from -12 to 12.

11x-12+12=-1+12

11x=11

Divide by 11 for both sides.

11x/11=11/11

Cross out 11 and 11, divide by 11 and then becomes x

x=1

Answer: x=1

User Houy Narun
by
4.6k points
5 votes

Answer:

x=1

Explanation:

4(2x-3)=-1-3x

8x -12 = -1 -3x

8x +3x = 12-1

11x = 11

x=1

User Eternalmatt
by
5.0k points